Revising an ESP Syllabus for International Relations: A Need Analysis-Based Study - Hariyanti, Yuni; Situmeang, Nurmasari; Setyaningsih, Endang (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
In an increasingly globalized world, knowledge of English has become critical for university graduates of all majors. English proficiency is not only required to access these opportunities, but it is also a prerequisite for competing in the international labour market. Despite its relevance, many graduates suffer difficulties as a result of their lack of English proficiency. Even though General English (GE) classes are widely available, they may not fully educate students for the unique demands of their future employment. This emphasizes the importance of English for Specific Purposes (ESP) courses, which are tailored to address the specific needs of students based on the Need Analysis (NA). However, in subjects such as International Relations (IR), research on ESP and NA remains limited. This study investigated students’ perceptions of the current English for International Relations (EFIR) syllabus and gathered feedback for its improvement. A descriptive qualitative approach was employed as part of a Research and Development (RD) study. Data were collected through questionnaires (n=60) and Focus Group Discussions (FGDs) (n=15). The study discovered that, while both basic (92%) and advanced EFIR students (96%) were generally satisfied with the syllabus, advanced students suggested adding more modern diplomatic themes, practical experiences, and interactive learning methodologies to increase engagement and knowledge. This study underscored the necessity of refining ESP syllabus based on student feedback to ensure its relevance and effectiveness. Future research should explore the long-term impact of these syllabus modifications on students’ professional readiness.